Impact of prediagnostic smoking and smoking cessation on colorectal cancer prognosis: a meta-analysis of individual patient data from cohorts within the CHANCES consortium. (13th December 2017) - Ordóñez-Mena, J M; Walter, V; Schöttker, B; Jenab, M; O'Doherty, M G; Kee, F; Bueno-de-Mesquita, B; Peeters, P H M; Stricker, B H; Ruiter, R; Hofman, A; Söderberg, S; et al.
Abstract: Background: Smoking has been associated with colorectal cancer (CRC) incidence and mortality in previous studies and might also be associated with prognosis after CRC diagnosis. However, current evidence on smoking in association with CRC prognosis is limited. Patients and methods: For this individual patient data meta-analysis, sociodemographic and smoking behavior information of 12 414 incident CRC patients (median age at diagnosis: 64.3 years), recruited within 14 prospective cohort studies among previously cancer-free adults, was collected at baseline and harmonized across studies. Vital status and causes of death were collected for a mean follow-up time of 5.1 years following cancer diagnosis. Associations of smoking behavior with overall and CRC-specific survival were evaluated using Cox regression and standard meta-analysis methodology. Results: A total of 5229 participants died, 3194 from CRC. Cox regression revealed significant associations between former [hazard ratio (HR) = 1.12; 95 % confidence interval (CI) = 1.04–1.20] and current smoking (HR = 1.29; 95% CI = 1.04–1.60) and poorer overall survival compared with never smoking. Compared with current smoking, smoking cessation was associated with improved overall (HR<10 years  = 0.78; 95% CI = 0.69–0.88; HR≥10 years  = 0.78; 95% CI = 0.63–0.97) and CRC-specific survival (HR≥10 years  = 0.76; 95% CI = 0.67–0.85). Conclusion: In this large meta-analysis including primary data of incident CRC patients from 14 prospective cohort studies on the association between smoking and CRC prognosis, former and current smoking were associated with poorer CRC prognosis compared with never smoking. Smoking cessation was associated with improved survival when compared with current smokers. Future studies should further quantify the benefits of nonsmoking, both for cancer prevention and for improving survival among CRC patients, in particular also in terms of treatment response.